OSH risk analysis with hazard identification risk assessment and control (HIRARC) method at NPK Fertilizer Production Department of PT X: Indonesia - Nuriah, Ayu Nitri; Rudyarti, Edwina (Periodicals of Occupational Safety and Health, 2023)
According to Menurut BPJS Ketenagakerjaan (Social Security Management Agency of Manpower), there has been a constant increase in occupational accidents in the last 7 years, where by 2022 it reached 265.334. The NPK factory of PT X is a petrochemical factory that produces NPK fertilizer. In it's production process, it needs nitrogen, phosphate, kalium and clay as it's raw materials. In addition to the chemical materials for it's production purposes, PT X utilizes modern machineries to make the process easier. From this description, it can be concluded that the production of NPK fertilizer would create a number of hazards which may lead to occupational accidents (OA) as well as occupational diseases (OD). This study aims to analyze the OSH risks which are present at the NPK factory of PT X using the method of Hazard Identification Risk Assessment and Risk Control. This is a quantitative study with observational descriptive approaches. It was found out that before the implementation of risk control, the NPK factory of PT X had the extreme risk rate of 75%, high risk rate of 14%, and medium risk rate of 3% from the total of 28 existing hazards (100%). Upon the implementation of control on the 28 hazards, PT X experienced the decrease in risk rates as follows: high risk 11%, medium risk 23%, and low risk 7%. Keywords: OSH risk analysis, Hazard Identification Risk Assessment And Control.